Investigation of thermodynamic parameters of Organic Rankine Cycle (ORC) designed exclusively to improve generating large-scale electricity purpose - Rowshanaie, Omid; Mustapha, Saari; Ahmad, Kamarul Arifin; Rowshanaie, Hooman (Scientific Online Publishing, 2014)
In present ORC thermodynamic cycle, R245fa, NOVEC700, and R141b as refrigerant working fluids sent to a Heat Exchanger then sent to an Expander to produce electricity, separately. Finally, the remaining working fluid is condensed by a Cooler and it is sent back to the ORC thermodynamic cycle. Current study conducted and analyzed the net power output of Expander, which R141b has a highest amount compare with R245fa, and NOVEC7000. The optimum pressure of working fluids at inlet of Expander has linear relationship with temperature of working fluids at inlet of Expander, with increasing the optimum pressure of working fluids at inlet of Expander, the temperature of working fluids at inlet of Expander is increasing slightly, and then net power Electricity of Expander is increasing, significantly. The efficiency of ORC and thermal efficiency for R245fa, NOVEC7000, and R141b measured at influence of inlet pressure of Expander differences which due to specific different inlet temperature of Expander. The highest, middle, and lowest of ORC efficiency belongs to the R245fa, R141b, and NOVEC7000, respectively. And the highest, middle, and lowest of thermal efficiency belongs to the R141b, NOVEC7000, and R245fa, respectively.